Building Human Capital : Lessons from Country Experiences – Morocco - Benkassmi, Mohamed; Abdelkhalek, Touhami (World Bank, Washington, DC, 2020)
This case study examines the policies, programs and processes undertaken in Morocco to improve its human capital outcomes since the 1990s. Sustained political commitment to education as a national priority across successive governments meant that while the net enrollment rate in primary school was 52.4 percent in 1990, by 2013 it has risen to over 98 percent. Not only are boys and girls enrolled at similar rates, rural areas were able to catch up to urban areas. Since 2000, investments in education have been large and sustained, between 5 and 6 percent of GDP. While still under implementation, the current strategic vision 2015-2030 seeks to provide equity and quality for all, particularly those from rural and less developed regions in Morocco. Just as the government has stepped up its investments in education it has sought to tackle a variety of health challenges simultaneously. Reductions in infant and maternal mortality, curbing the fertility rate, limiting communicable and non-communicable diseases and improving the nutritional status of Moroccan children were prioritized not only through the development and better geographic distribution of health care services but also by encouraging a shift towards health insurance coverage in order to help citizens, particularly the poor, afford health care. A diligent immunization policy meant that 91 percent of Moroccan children are fully immunized. Coupled with this has been careful management of communicable diseases, including through the use of international partnerships. As the country grapples with the next wave of challenges, the case study proposed the need to pursue more integrated multisectoral policies that not only address the interplay between health and education but a broad range of sectors including but not limited to transport, infrastructure, and the labor market. It proposes the broad outlines of a series of actions that will be critical to continue to build the human capital of generations to come.